1991
DOI: 10.1063/1.460674
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate effects on photoemission from Ag

Abstract: We have used pyridine and a number of related molecules to lower the workfunction of thin Ag films so as to compare the effects of various molecular properties on the photoemission process and on surface electronic modes. We find that a nitrogen lone pair electronic orbital is essential for a large threshold shift. Other molecular properties, such as dipole moment and polarizability have a very small effect. The films are rough, therefore we see strong photoyields at the energy of the surface plasma mode, 3.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…4(a)]. This is within the range of WF values found in the literature for macroscopic silver, 10,15,[54][55][56][57] meaning that the particles are metallic. Various studies [58][59][60] on free Ag clusters/nanoparticles showed that the macroscopic polycrystalline silver WF is likely to be 4.25 eV.…”
Section: Resultssupporting
confidence: 75%
“…4(a)]. This is within the range of WF values found in the literature for macroscopic silver, 10,15,[54][55][56][57] meaning that the particles are metallic. Various studies [58][59][60] on free Ag clusters/nanoparticles showed that the macroscopic polycrystalline silver WF is likely to be 4.25 eV.…”
Section: Resultssupporting
confidence: 75%
“…14 Less attention has been given to the effect of organic adsorbate on the efficiency of photoelectron emission, and only a few works on the subject have been published. 15,16 Electron transmission through organic thin films condensed on metal substrates has been investigated in the past mainly by low-energy electron-transmission (LEET) spectroscopy. 17 It was suggested that for films of saturated hydrocarbon chains of various lengths, the low-energy electron transmission is governed mainly by the film electronic band structure.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Similarly, LEET experiments were performed on solid water . Less attention has been given to the effect of organic adsorbate on the efficiency of photoelectron emission, and only a few works on the subject have been published. , …”
Section: Experimental Backgroundmentioning
confidence: 99%
“…A number of phenomena, such as surface-enhanced Raman scattering (SERS), photodissociation of organic molecules, or photoemission of electrons at the Ag/vacuum and Ag/solution interfaces, were found to depend strongly on the morphology of the silver metal surface. Procedures for the preparation of microscopically rough silver surfaces used in such studies involved chemical etching, electrochemical roughening, mechanical polishing of Ag with varying size of alumina, and metal sputtering in vacuum on various pre-etched substrates.…”
Section: Introductionmentioning
confidence: 99%